Multimodality diagnostic imaging in tuberculous lymphadenitis - a case review - Nordin, Abdul Jalil; Mohd Saini, Suraini; Abdul Razak, Hairil Rashmizal; Abdul Rahim, Noraini (Universiti Putra Malaysia Press, 2011)
The purpose of this article is to demonstrate the appearance of active TB lymphadenitis using multimodality imaging apparatus. Multi-modality diagnostic imaging tools, including chest radiograph, Ultrasound (US), Computed Tomographic Scan (CT), Magnetic Resonance Imaging (MRI), and integrated 18F-FDG Positron Emission Tomography/CT examination, were performed to demonstrate TB lymphadenitis in the neck and superior mediastinum of a 26 year old female patient. There was widening of superior mediastinum on chest radiograph. Meanwhile, the ultrasound carried out detected superficial cystic lesions in the cervical region. The MRI found multiple gadolinium enhanced cervical and mediastinal lymphadenophaties. Contrast enhanced CT found heterogeneous enhancing lymphadenopathies in the same anatomical region. FDG PET/CT demonstrated a high metabolic activity in all lesions, as demonstrated by conventional imaging modalities. Mycobacterium tuberculosis was isolated from 1ml aspirate using US guidance. Post-treatment FDG PET CT scan demonstrated a complete metabolic remission of active lesions FDG PET CT can be used to demonstrate metabolic activity of active TB lesions in addition to guide clinicians in treating TB lesions.